SYNTHESIS AND ANTIMICROBIAL ACTIVITY OF 1-(2'',4''- DICHLOROPHENYL)-3-(SUBSTITUTED ARYL)-2-PROPENE-1-ONES: Pharmaceutical Science-Medicinal Chemistry - MOHAMMAD, FAQRODDIN; S.A.RAHAMAN; MD.MOINUDDIN (International Journal of Life Science and Pharma Research, 2012)
According to Claisen-Schmidt condensation a series of eight novel chalcones were synthesised by condensing 2,4-Dichloro acetophenone with various aromatic aldehydes in dilute ethanolic potassium hydroxide solution at room temperature. All these compounds were characterized by means of their IR, 1H NMR spectroscopic data and elemental analysis. The antimicrobial activity of these compounds was evaluated by the cup plate method. The particular compounds FC-4,6,7,8 showed maximum antibacterial acitivity because of having electron releasing groups such as methoxy (FC-4) and naphthyl groups (FC-8). Similarly compounds FC-1,2,3 halogen having pharmacophores such as chloro, dichloro and bromo groups exhibited moderate to considerable antifungal activity. These results suggest that the chalcone derivatives have excellent scope for further development as commercial antimicrobial agents.